Dela Web-Based Laundry Information System Using the Codeigniter Framework - Nur Khafidhoh; Adela Fiatindra Agasti; Sujono Sujono (LPPM Universitas KH. A. Wahab Hasbullah, 2026)
Dela Laundry, a laundry business in Banggle Hamlet, Losari Village, Ploso Subdistrict, is still experiencing operational problems due to the use of manual record-keeping. This has the potential to cause data errors, delays in information, and reduce customer satisfaction. Therefore, a web-based information system is needed to speed up the service process, minimize the risk of errors, and provide transparency of the laundry process to customers. As a solution, this study designs and develops a Laundry Information System using the CodeIgniter 4 framework with PHP programming language and MySQL database. The development method used is the Waterfall model, which includes the stages of requirement analysis, system design, implementation, testing, and maintenance. This system aims to facilitate administrators and staff in managing customer data, orders, services, and reports, as well as allowing customers to monitor the status of their laundry orders online without needing to log in. Testing results using the Black Box Testing method showed that all system functions operated properly without any significant errors being detected. In addition, a feasibility test conducted through a questionnaire to users obtained an average score of 88%, which falls into the “Good” category and is suitable for use. Thus, this system is capable of making operational processes more structured, efficient, and transparent, as well as increasing customer satisfaction and supporting the development of small to medium-scale laundry businesses.